Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1111/j.1530-0277.1998.tb03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pentylenetetrazole on Ethanol Intake, Ethanol Kinetics, and Social Behavior in Male Wistar Rats

Abstract: Stress and anxiety are often implicated in excessive alcohol use. The nature of this interaction, however, is not understood. The aim of this study was to examine the effect of the anxiogenic agent, pentylenetetrazole (PTZ), on the acquisition and maintenance of ethanol drinking behavior in male Wistar rats. In rats maintained on a limited access procedure, with a choice between a 12% w/v ethanol (ETOH) solution and water available for 30 min each day, acute PTZ administration (1.5 to 15.0 mg/kg) did not modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This possibility, however, is unlikely because several studies reported that exposure to "anxiogenic" agents such as Ro15-4513 or pentylenetrazol do not increase alcohol consumption (Petry 1995; Buczek et al 1997Buczek et al , 1998. In addition, our attempts to mimic the effect of footshock stress on reinstatement of heroin or alcohol seeking (see LÞ et al 1998;Shaham et al 2000) with "anxiogenic" compounds such as FG-7142 or pentylenetetrazole were not successful (unpublished data).…”
Section: Methodological Considerationsmentioning
confidence: 53%
“…This possibility, however, is unlikely because several studies reported that exposure to "anxiogenic" agents such as Ro15-4513 or pentylenetrazol do not increase alcohol consumption (Petry 1995; Buczek et al 1997Buczek et al , 1998. In addition, our attempts to mimic the effect of footshock stress on reinstatement of heroin or alcohol seeking (see LÞ et al 1998;Shaham et al 2000) with "anxiogenic" compounds such as FG-7142 or pentylenetetrazole were not successful (unpublished data).…”
Section: Methodological Considerationsmentioning
confidence: 53%
“…Testing in an arena lit by high light and with which the rats are familiar was selected for this study, since in this condition it is possible to detect both increases and decreases in anxiety (File 1980(File , 1993. The social interaction test has proved sensitive to a wide range of anxiolytic drugs (File et al 1976;File 1980;Barnes et al 1990;Lightowler et al 1994) and to the anxiogenic effects of drugs and neuropeptides (File and Vellucci 1978;File and Clarke 1980;File and Lister 1984;Niesink and van Ree 1984;Guy and Gardner 1985;File et al 1986File et al , 1988Pellow and File 1986;Dunn and File 1987;Sams-Dodd 1995;Bhattacharya et al 1997;Buczek et al 1998;Sajdyk et al 1999). The anxiogenic state that is induced by withdrawal from chronic treatment of benzodiazepines, ethanol, caffeine and nicotine can also be detected using this test (File et al 1989;Costall et al 1990;File and Andrews 1991;File et al 1991File et al , 1992Andrews et al 1997;Bhattacharya et al 1997;Irvine et al 1999).…”
Section: Introductionmentioning
confidence: 98%